Cue-Reactivity Among Young Adults With Problematic Instagram Use in Response to Instagram-Themed Risky Behavior Cues: A Pilot fMRI Study - Nasser, Nisha Syed; Sharifat, Hamed; Rashid, Aida Abdul; Hamid, Suzana Ab; Rahim, Ezamin Abdul; Loh, Jia Ling; Ching, Siew Mooi; Hoo, Fan Kee; Ismail, Siti Irma Fadillah; Tyagi, Rohit; Mohammad, Mazlyfarina; Suppiah, Subapriya (Frontiers in Psychology, 2020)
Background: Problematic Instagram Use (PIGU), a Specific type of Internet Addiction, is prevalent among adolescents and young adults. In certain instances, Instagram acts as a platform for exhibiting photos of risk-taking behaviour that the subjects with PIGU upload to gain “Likes” as a surrogate for gaining peer acceptance and popularity. Aims: The primary objective was to evaluate whether addiction-specific cues compared with neutral cues i.e. ‘Negative Emotional Valence’ cues vs 'Positive Emotional Valence' cues, would elicit activation of the dopaminergic reward network (i.e. Precuneus, Nucleus Accumbens, Amygdala) and consecutive deactivation of the executive control network (i.e. medial prefrontal cortex (mPFC) and dorsolateral prefrontal cortex (dlPFC), in the PIGU subjects. Method: An fMRI cue-induced reactivity study was performed using 'Negative-Emotional-Valence', 'Positive-Emotional-Valence’, and 'Truly Neutral' cues, using Instagram themes. Thirty subjects were divided into PIGU and healthy control (HC) groups, based on a set of diagnostic criteria using behavioural tests, including the Modified Instagram Addiction Test (IGAT), to assess the severity of PIGU. In-scanner recordings of the subjects' responses to the images and regional activity of the neural addiction pathways were recorded. Results: 'Negative-Emotional-Valence' > 'Positive-Emotional-Valence’ cues elicited increased activations in the precuneus in the PIGU group. A negative and moderate correlation was observed between PSC at the right mPFC with the IGAT scores of the PIGU subjects when corrected for multiple comparisons [r = -0.777, (p < 0.004, two-tailed)]. Conclusion: Addiction-specific Instagram-themed cues identify the neurobiological underpinnings of Instagram addiction. Activations of the dopaminergic reward system and deactivation of the executive control network indicate converging neuropathological pathways between Instagram addiction and other types of addictions.